ETIOLOGICAL FACTORS CAUSING HYPERTENSION DISEASE AND MEASURES TO CONTROL IT (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article talks about hypertension, which is widespread among the population and is the most common among cardiovascular diseases. Hypertension, high blood pressure is the factor that plays the most important role in the development of cardiovascular diseases, the most dangerous of such complications are heart attack and stroke. Most elderly people suffer from this problem, but nowadays high blood pressure is also found in middle-aged and young people. When is the blood pressure reading considered dangerous? How is first aid given during a hypertensive crisis? What measures should be taken in the early stages of high blood pressure? You can find answers to such questions in this article.